A Discourse Analytical Study of Conceptual Metaphors in Selected Arabic Songs - Mubarak, Ahmed Sahib; Al-Fayadh, Sameerah Atshan (International Journal of Psychosocial Rehabilitation, 2020)
This study is intended to investigate the use of conceptual metaphors in translated Arabic songs. It tries to figure out the ways via which conceptual metaphors are expressed in the Arabic songs and to identify the communicative functions behind these usages. To achieve these aims, the study presents a concise outline of Lakoff and Johnson’s (2003) conceptual metaphor theory then it analyses two Arabic songs titled Liel elBanafsadg (The Violet’s Night) by Muzzaffar Al-Nawwab and Kalimat (Words) by Nizar Qabbani. The study finds out that flirt is the communicative function commonly employed in conceptual metaphors followed by integrity and panegyric. It is concluded that Al-Nawwab and Qabbani employ conceptual metaphors effectively in their songs to express different communicative functions.